Association of Spouse Deployment on Pregnancy Outcomes in a U.S. Military Population. Issue 3 (September 2015) - Tarney, Christopher M.; Berry-Caban, Cristobal; Jain, Ram B.; Kelly, Molly; Sewell, Mark F.; Wilson, Karen L.
Abstract : OBJECTIVE: To evaluate the association of spousal deployment during the antenatal period on maternal and neonatal outcomes and to estimate whether group prenatal care may be beneficial in reducing adverse outcomes when spouses are deployed. METHODS: Primigravid women who delivered at Womack Army Medical Center, Fort Bragg, North Carolina, were prospectively enrolled and selected for participation on a random basis between January 2013 and January 2014. Women whose spouses were deployed to a combat zone during the entire pregnancy (deployed group) were compared with women whose spouses were not deployed during the pregnancy (nondeployed group). Pregnancy and neonatal outcomes were compared between groups. RESULTS: Three hundred ninety-seven women were enrolled with 183 (46.1%) in the deployed group and 214 (53.9%) in the nondeployed group. Spouse deployment was associated with increased risk of preterm delivery (38 [20.8%] compared with 16 [7.5%], P<. 001) and postpartum depression (30 [16.4%] compared with 13 [6.1%], P= .001) when compared with women in the nondeployed group. There were no differences in the incidence of preterm delivery and postpartum depression for women in the deployed group who participated in group prenatal care when compared with women participating in traditional care (preterm delivery 6 [14.6%] compared with 32 [22.5%], P= .38; postpartum depression 4 [9.8%] compared with 26 [18.3%], P =.24). CONCLUSION: Women who have a spouse deployed during their pregnancy are at increased risk for preterm birth and postpartum depression. Larger studies are needed to evaluate whether spouse deployment during pregnancy has other perinatal effects and whether group prenatal care may have a positive effect on adverse perinatal outcomes in this population. LEVEL OF EVIDENCE: II Abstract : Spouse deployment to a combat zone during pregnancy is associated with an increased risk for preterm delivery and postpartum depression.